Local delivery of cancer-cell glycolytic inhibitors in high-grade glioma - Wicks, Robert T. (Neuro Oncol, 2015)
BACKGROUND: 3-bromopyruvate (3-BrPA) and dichloroacetate (DCA) are inhibitors of cancer-cell specific aerobic glycolysis. Their application in glioma is limited by 3-BrPA's inability to cross the blood-brain-barrier and DCA's dose-limiting toxicity. The safety and efficacy of intracranial delivery of these compounds were assessed. METHODS: Cytotoxicity of 3-BrPA and DCA were analyzed in U87, 9L, and F98 glioma cell lines. 3-BrPA and DCA were incorporated into biodegradable pCPP:SA wafers, and the maximally tolerated dose was determined in F344 rats. Efficacies of the intracranial 3-BrPA wafer and DCA wafer were assessed in a rodent allograft model of high-grade glioma, both as a monotherapy and in combination with temozolomide (TMZ) and radiation therapy (XRT). RESULTS: 3-BrPA and DCA were found to have similar IC(50) values across the 3 glioma cell lines. 5% 3-BrPA wafer-treated animals had significantly increased survival compared with controls (P = .0027). The median survival of rats with the 50% DCA wafer increased significantly compared with both the oral DCA group (P = .050) and the controls (P = .02). Rats implanted on day 0 with a 5% 3-BrPA wafer in combination with TMZ had significantly increased survival over either therapy alone. No statistical difference in survival was noted when the wafers were added to the combination therapy of TMZ and XRT, but the 5% 3-BrPA wafer given on day 0 in combination with TMZ and XRT resulted in long-term survivorship of 30%. CONCLUSION: Intracranial delivery of 3-BrPA and DCA polymer was safe and significantly increased survival in an animal model of glioma, a potential novel therapeutic approach. The combination of intracranial 3-BrPA and TMZ provided a synergistic effect.